High‐Pressure‐Induced Comminution and Recrystallization of CH3NH3PbBr3 Nanocrystals as Large Thin Nanoplates. Issue 2 (27th November 2017) - Yin, Tingting; Fang, Yanan; Chong, Wee Kiang; Ming, Koh Teck; Jiang, Shaojie; Li, Xianglin; Kuo, Jer‐Lai; Fang, Jiye; Sum, Tze Chien; White, Timothy J.; Yan, Jiaxu; Shen, Ze Xiang
Abstract: High pressure (HP) can drive the direct sintering of nanoparticle assemblies for Ag/Au, CdSe/PbS nanocrystals (NCs). Instead of direct sintering for the conventional nanocrystals, this study experimentally observes for the first time high‐pressure‐induced comminution and recrystallization of organic–inorganic hybrid perovskite nanocrystals into highly luminescent nanoplates with a shorter carrier lifetime. Such novel pressure response is attributed to the unique structural nature of hybrid perovskites under high pressure: during the drastic cubic–orthorhombic structural transformation at ≈2 GPa, (301) the crystal plane fully occupied by organic molecules possesses a higher surface energy, triggering the comminution of nanocrystals into nanoslices along such crystal plane. Beyond bulk perovskites, in which pressure‐induced modifications on crystal structures and functional properties will disappear after pressure release, the pressure‐formed variants, i.e., large (≈100 nm) and thin (<10 nm) perovskite nanoplates, are retained and these exhibit simultaneous photoluminescence emission enhancing (a 15‐fold enhancement in the photoluminescence) and carrier lifetime shortening (from ≈18.3 ± 0.8 to ≈7.6 ± 0.5 ns) after releasing of pressure from 11 GPa. This pressure‐induced comminution of hybrid perovskite NCs and a subsequent amorphization–recrystallization treatment offer the possibilities of engineering the advanced hybrid perovskites with specific properties. Abstract : High pressure (up to tens of gigapascals), as a clean and powerful tool, can effectively alter crystal structures. It is experimentally investigated for the first time whether pressure can regulate the comminution and recrystallization of MAPbBr3 nanocrystals. The initial nanocrystals slide into nanoslices during phase transformation to the orthorhombic polymorph, followed by recrystallization into nanoplates upon amorphization.